2011
DOI: 10.1186/1471-2407-11-429
|View full text |Cite
|
Sign up to set email alerts
|

A novel splice variant of the stem cell marker LGR5/GPR49 is correlated with the risk of tumor-related death in soft-tissue sarcoma patients

Abstract: BackgroundThe human leucine-rich, repeat-containing G protein-coupled receptor (LGR) 5, also called GPR49, is a marker of stem cells in adult intestinal epithelium, stomach and hair follicles. LGR5/GPR49 is overexpressed in tumors of the colon, ovary and liver and in basal cell carcinomas. Moreover, an expression in skeletal muscle tissues was also detected. However, there has been no investigation regarding the expression and function of LGR5/GPR49 in soft-tissue sarcomas (STS) yet.MethodsSeventy-seven frozen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 22 publications
0
23
0
Order By: Relevance
“…Data to support a potential role for LGR5 in tumors of mesenchymal origin is also now beginning to emerge. A recent report by Rot et al (2011) described a novel splice variant of LGR5 in the context of soft tissue sarcoma and reported that low level expression of this variant transcript (which lacks exon 5) was associated with worse overall and event free survival. In addition, the LGR5 locus was recently identified to be among the most frequently amplified loci in a genome-wide study of soft tissue sarcomas (copy number in top 1% of nearly 19,000 genes) suggesting that up-regulation of LGR5 may contribute to sarcoma pathogenesis (Barretina et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Data to support a potential role for LGR5 in tumors of mesenchymal origin is also now beginning to emerge. A recent report by Rot et al (2011) described a novel splice variant of LGR5 in the context of soft tissue sarcoma and reported that low level expression of this variant transcript (which lacks exon 5) was associated with worse overall and event free survival. In addition, the LGR5 locus was recently identified to be among the most frequently amplified loci in a genome-wide study of soft tissue sarcomas (copy number in top 1% of nearly 19,000 genes) suggesting that up-regulation of LGR5 may contribute to sarcoma pathogenesis (Barretina et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was characterized as a marker for stem cells in soft tissue sarcoma (38). In this study, we attempted to use antibodies to LGR5 as a marker for stem cells in human colon cancer.…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, many studies have revealed that LGR5 is overexpressed in various types of tumors, including colorectal cancer[ 15 ], ovarian tumor[ 16 ], hepatocellular carcinoma[ 17 ], basal cell carcinoma[ 18 ], and esophageal adenocarcinoma[ 19 ]. High LGR5 expression is associated with the initiation, invasion, and metastasis of tumors[ 20 , 21 ], suggesting the potential role of LGR5 in tumorigenesis. Additionally, LGR5 has been recognized as a cancer stem cell marker for colorectal cancers[ 22 ].…”
Section: Introductionmentioning
confidence: 99%